Application of Technology on Improving Beef Cattle Productivity in East Nusa Tenggara - B, Wirdahayati R (Indonesian Animal Sciences Society, 2010)
The Province of East Nusa Tenggara (NTT) had been one of the major beef cattle suppliers under traditional management system in Indonesia. The beef cattle farming that based on grazing native pasture and the introduction of shrub legumes (Leucaena leucocephala) may contribute to around 15 â 50% of the farmersâ household income. In the last few years, supply of beef cattle tended to decline due to the decrease in cattle population in NTT. Some basic improvements in management and feeding toward increasing beef cattle productivities had been carried out in Nusa Tenggara, such as a baseline survey on Cattle Health and Productivity Survey (CHAPS) conducted in 1990 â 1992. The objective of the program was to identify the existing beef cattle productivity and health condition throughout Nusa Tenggara. A collaborative research with the Ministry of Research and Technology (Integrated Prime Research) had also been carried out and the result showed that early weaning in Bali calves that can be practised as early as 3 â 6 months to prevent calves losses during the dry season. A program of the Assessment on Beef Cattle Base Farming Activities had also been conducted to improve fattening and breeding practices through the improvement in beef cattle management and feeding systems. At the latest development, fattening scheme has been introduced under a partnership approach involving private sectors and cooperatives. This needs to be facilitated by the government to accelerate the program such as access to capital and intensive extension services to build farmers awareness toward profit oriented beef cattle farming. Optimalization of the available potential resources and technology in NTT, will be an opportunity to enhance beef cattle production and gains back the reputation as one of the major producing beef cattle in the past. This will also support the national livestock program nowadays, called Beef Cattle Self Sufficiency Program 2014. Key words: Beef cattle, productivity, technology, East Nusa Tenggara